Standardized universal pulse: A fast RF calibration approach to improve flip angle accuracy in parallel transmission - Le Ster, Caroline; Mauconduit, Franck; Massire, Aurélien; Boulant, Nicolas; Gras, Vincent (Magnetic resonance in medicine, 2022)
Purpose In parallel transmission (pTX), subject‐tailored RF pulses allow achieving excellent flip angle (FA) accuracy but often require computationally extensive online optimizations, precise characterization of the static field (ΔB0), and the transmit RF field (B1+) distributions. This costs time and requires expertise from the MR user. Universal pulses (UPs) have been proposed to reduce this burden, yet, with a penalty in FA accuracy. This study introduces the concept of standardized universal pulses (SUPs), where pulses are designed offline and adjusted to the subject through a fast online calibration scan. Methods A SUP is designed offline using a so‐called standardized database, wherein each B1+ map has been normalized to a reference transmit RF field distribution. When scanning a new subject, a 3‐slice B1+ acquisition (scan time <10 s) is performed and used to adjust the SUP to the subject through a linear transform. SUP performance was assessed at 7T with simulations by computing the FA‐normalized root mean square error (FA‐NRMSE) and the FA pattern stability as measured by the average and coefficient of variation of the FA across 15 control subjects, along with in vivo experiments using an MP2RAGE sequence implementing the SUP variant for the FLASH readout. Results Adjusted SUP improved the FA‐NRMSE (8.8% for UP vs. 7.1% for adjusted SUP). Experimentally in vivo, this translated in an improved signal homogeneity and more accurate T1 quantification using MP2RAGE. Conclusion The proposed SUP approach improves excitation accuracy (FA‐NRMSE) while preserving the same offline pulse design principle as offered by UPs.